Active Charcoal from Palm Kernel Shells as a Catalyst in The Production of Biodiesel (Universitas Negeri Semarang, 2020)
Palm kernel shells are one of the main wastes for processing of palm oil. Palm kernel shells are waste that can be used as a catalyst in the biodiesel production. Besides many natural ingredients, the price of catalyst prepared from these materials is also relatively cheap compared to other catalysts, make the biodiesel production more sustainable, and environmentally friendly. This study aims to make activated carbon from palm shell through the process of carbonization and chemical activation. The carbonization process was carried out at 550oC for 3 hours until charcoal was formed. While the activation process was carried out using ZnCl2 activators with concentrations of 0.1 M, 0.25 M, 0.5 M and 1 M which were activated for 4 hours at 90oC. Â Based on the results of the FTIR analysis the presence of O-H and C-O bonds indicates that the carbon produced from the palm kernel shell tends to be polar (volatile). Thus the charcoal produced can be used as catalyst in the biodiesel production. For the SEM test results, it can be seen morphologically that more pore crystals are added and are still brittle at a ZnCl2 concentration of 0.1 M. Based on FTIR and SEM analysis, the best activated charcoal was activated charcoal with a concentration of 0.25 M ZnCl2.